MO1006: Cni-Induced Hypomagnesemia in Kidney Transplantation: A Comparative Monocentric Study Between Sucrosomial Magnesium and Magnesium Pidolate. (3rd May 2022) - Federica Stefanelli, Lucia; Alessi, Marianna; Gobbi, Laura; Innico, Georgie; Bertoldi, Giovanni; Ravarotto, Verdiana; Calò, Lorenzo
Abstract: BACKGROUND AND AIMS: Magnesium (Mg) is the second cation in the intracellular space and the fourth prevalent cation in the body. It contributes to DNA and protein synthesis, infiammatory processes and cardiac excitability, while Mg deficiency leads to increased cardiovascular risk, atherosclerosis and diabetes [1]. In addition to gastrointestinal losses, loop or thiazide diuretics induce renal wasting, volume expansion and nephrotoxins including antibiotics Hypomagnesemia (HypoMg) is observed early after kidney transplantation and is associated with a faster decline of allograft function. Main determinants are calcineurin inhibitors (CNIs ), protonic pump inhibitors (PPI), low Mg intake and diuretics. CNIs, in particular, induce HypoMg with mechanisms not fully understood, likely via downregulation of the Mg channel TRPM6 in the distal collecting tubule [2]. HypoMg should be corrected with oral supplements. Recently, in order to increase magnesium bioavailability and tolerance not shown by convetional oral magnesium supplements, a new sucrosomial magnesium formulation has been developed. Its innovative preparation encapsulates magnesium oxide in a phospholipid membrane covered by a sucrester matrix, which enhances Mg passage through the gastric and intestinal environment without any interaction with the intestinal mucosa [3]. This study evaluates magnesium bioavailability, tolerance and effectiveness after administration of sucrosomial magnesium compared with magnesium pidolate. METHOD: We recruited 32 adult single, double or combined kidney-pancreas transplant recipients within 1 year from transplantation, who developed CNI-induced hypomagnesemia. Exclusion criteria include: HypoMg due to PPI or gastrointestinal losses. A total of 13 patients received magnesium pidolate, and 19 patients received sucrosomial magnesium. Venous blood samples were taken at baseline (T0 ) and after 10 days of magnesium supplement (T1 ). RESULTS: Sucrosomial magnesium increased Mg bioavailability and tolerance: 0.60 ± 0.02 T0 mmoL/L versus 0.69 ± 0.05 T1 ; P < .0001 versus magnesium pidolate: 0.61 ± 0.05 T0 versus 0.64 ± 0.05 T1 ; P = .72 N.S. (Fig. 1A). Sucrosomial magnesium provided an increase of Mg over magnesium pidolate in terms of $Δ % $ increase: 12.4% for sucrosomial Mg versus 5.4%, P = .04 (Fig. 1B). CONCLUSION: Our data, although obtained by a small cohort of transplant patients, shows that sucrosomial Mg is more efficient and better tolerated compared with magnesium pidolate. On the one hand, the fact that our study is the first in transplant patients to evaluate the impact of sucrosomial Mg for the correction of HypoMg might justify the limited number of patients enrolled and the short observation time; on the other hand, our results could serve as a working hypothesis for further studies with a larger number of transplant patients and for extended study duration to confirm the benefit of sucrosomial Mg.